1995
DOI: 10.1159/000282691
|View full text |Cite
|
Sign up to set email alerts
|

Electrovesicography in Interstitial Cystitis

Abstract: An electrovesicogram (EVG) was performed in 9 women (mean age 44.6 years) with interstitial cystitis (IC) to characterize an electrovesicographic pattern for diagnostic purposes. Seven healthy women acted as controls. One electrode was located above and lateral to each pubic tubercle and a 3rd above the symphysis pubis. A reference electrode was applied to the lower limb. Recording was done in both the full and empty urinary bladder. Pacesetter potentials (PPs) were registered in the normal women as triphasic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This technique has previously been described [23,24]. In brief, the subject was asked to abstain from urination for at least 4 hours prior to testing.…”
Section: Technique Of Transcutaneous Electrovesicographymentioning
confidence: 99%
See 4 more Smart Citations
“…This technique has previously been described [23,24]. In brief, the subject was asked to abstain from urination for at least 4 hours prior to testing.…”
Section: Technique Of Transcutaneous Electrovesicographymentioning
confidence: 99%
“…Recent studies have shown that the urinary bladder possesses electrical activity [22][23][24]. A normal electrovesicogram (EVG) could be identified in experimental animals and in humans [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations